2019
DOI: 10.1007/s11192-019-03211-y
|View full text |Cite
|
Sign up to set email alerts
|

Metrics-based profiling of university research engagement with Africa: research management, gender, and internationalization perspective

Abstract: U.S. university engagement with Africa in various areas including global health, education, environment, and agriculture has grown in the last 15 years. However, there is limited literature that acknowledges the scholarly output and impact of U.S.-Africa university research collaboration in support of their respective institutions' comprehensive internationalization goals. Using Michigan State University (MSU)-a public, research-intensive, land grant university with long history of engagement with Africa, as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…Bibliometrics has been used extensively to analyze research systems at the global, country and institutional levels and is based on bibliographic information on the enumeration and statistical analysis of scientific output in the form of peer-reviewed journal articles, publications, citations, patents, and other more complex indicators (Goffman and Harmon, 1971 ; Melin and Persson, 1996 ; Okubo, 1997 ; Wagner and Leydesdorff, 2005 ). Advanced bibliometric methods and visualization techniques (e.g., network maps based on keyword analysis) backed with various forms of analytics has further enhanced the value of bibliometric indicators to present and analyze research activities, emerging research areas, and new clusters of knowledge (Moya-Anegon et al, 2005 ; Small, 2006 ; Skupin, 2009 ; Upham and Small, 2010 ; Payumo and Sutton, 2015 ; Payumo et al, 2019 ). A number of studies have recognized the value of bibliometrics for understanding the link of gender and STI, for example the gender gap in various disciplines such as medicine, and in recognizing gender disparities in research output and collaboration patterns (Soderlund and Madison, 2015 ; Elsevier, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Bibliometrics has been used extensively to analyze research systems at the global, country and institutional levels and is based on bibliographic information on the enumeration and statistical analysis of scientific output in the form of peer-reviewed journal articles, publications, citations, patents, and other more complex indicators (Goffman and Harmon, 1971 ; Melin and Persson, 1996 ; Okubo, 1997 ; Wagner and Leydesdorff, 2005 ). Advanced bibliometric methods and visualization techniques (e.g., network maps based on keyword analysis) backed with various forms of analytics has further enhanced the value of bibliometric indicators to present and analyze research activities, emerging research areas, and new clusters of knowledge (Moya-Anegon et al, 2005 ; Small, 2006 ; Skupin, 2009 ; Upham and Small, 2010 ; Payumo and Sutton, 2015 ; Payumo et al, 2019 ). A number of studies have recognized the value of bibliometrics for understanding the link of gender and STI, for example the gender gap in various disciplines such as medicine, and in recognizing gender disparities in research output and collaboration patterns (Soderlund and Madison, 2015 ; Elsevier, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Hal ini juga tidak menutup kemungkinan bahwa Wanita juga turut berperan dalam pengembangan program penelitian. Payumo et al (2019) menyatakan bahwa dalam hasil risetnya membuktikan keterlibatan perempuan dalam memajukan pengetahuan dan inovasi global dalam upaya menghadapi masalah sosial ekonomi. Tidak hanya dalam hal penelitian, beberapa peluang karir saat ini masih banyak yang belum diisi atau memberikan tempat kepada Wanita.…”
Section: Peran Wanita Dalam Manajemen Penelitian Globalunclassified
“…In Africa, increasing coauthored papers in the Web of Science are used to justify the benefits of external research funds in Ghana to the point that 92% of research in public universities, 98% of research in government institutions, and 76% of collaborations of Ghana shown are written in international cooperation (Owusu-Nimo & Boshoff, 2017). Payumo et al (2019) add to the visualized benefits of cooperation with Africa for African countries gender parity externalities through the increasing participation of women in international research collaboration. Through comparing publication trends, international branch campuses in Asia (Qatar, the United Arab Emirates, and Malaysia) are also found to be "collectively (...) more international than their host countries and individually more international than their home campuses" (Pohl & Lane, 2018, p. 1731.…”
Section: Decolonial and Bibliometric Perspectives Of Research Cooperamentioning
confidence: 99%
“…To what extent does current scientific collaboration act as a form of neocolonial control that is exerted through knowledge production? Most studies on research partnerships (Baud, 2002; Mazzoleni & Nelson, 2007) and contemporary bibliometric analysis of research partnerships (Aldieri et al, 2018; Belter et al, 2019; Eduan & Yuanqun, 2018; Owusu-Nimo & Boshoff, 2017; Payumo et al, 2019; Pohl & Lane, 2018) seem to take for granted the positive outcomes of research collaboration for all parties through identifying social and educational conditions that enable scientific networks. Reflections on potential power relationships inherited from colonial legacies, however, are usually absent in this literature.…”
Section: Introductionmentioning
confidence: 99%